Influence of longitudinal rebars and boundary elements on the performance of 3D sandwich walls in direct compression - Rao, G. Appa; Poluraju, P. (Journal of Structural Engineering, 2024)
3D sandwich precast concrete walls are often used in building construction due to their superior performance, thermal efficiency, and speed of fabrication. An extensive literature review on the behaviour of solid walls has been reported. This paper reports on experimental investigations on 3D sandwich walls of 150mm thickness, formed with interior and exterior layers of concrete, separated by 50mm thick layer of insulation material. The performance of 3D sandwich walls under axial compression vis-a-vis influence of longitudinal reinforcement and boundary elements is discussed. Eight full-scale and one-third scale wall classified as slender and squat walls were tested to study the behavior and ultimate axial compressive strength. The structural properties including load-deformation response, crack initiation, and crack propagation under axial line loading have been discussed. It has been observed that the 3D sandwich walls exhibited composite behavior under axial compression up to ultimate stage. The ultimate load carrying capacity of 3D sandwich walls has been observed to be reduced gradually with increase in slenderness ratio. The experimental observations have been compared with the provisions of various codes of practice. The Indian and ACI code provisions along with other empirical expressions developed for estimating the carrying capacity of solid walls are compared for their applicability to 3D sandwich walls.